2006
DOI: 10.1111/j.0906-7590.2006.04457.x
|View full text |Cite
|
Sign up to set email alerts
|

Moose and vole browsing patterns in experimentally assembled pure and mixed forest stands

Abstract: Vehviläinen, H. and Koricheva, J. 2006. Moose and vole browsing patterns in experimentally assembled pure and mixed forest stands. Á Ecography 29: 497 Á506.Plants growing in diverse communities are believed to exhibit associational resistance to herbivores, but this hypothesis has seldom been tested experimentally for vertebrate herbivores in forest ecosystems. We examined browsing patterns of the two principal mammalian herbivores of Finnish boreal forests, moose and voles, in young stands where tree species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 49 publications
5
47
2
1
Order By: Relevance
“…Fertile habitats offer moose not only better quality and a larger quantity of food but also a variety of alternative food plants (Niemelä and Danell 1988;Heikkilä 1990;Heikkilä and Härkönen 1993;Månsson 2009;Nikula et al 2008). Pine stands mixed with deciduous seedlings seem to be attractive pastures for moose (Heikkilä 1990;Vehviläinen and Koricheva 2006), especially when birches are overtopping the pine seedlings (Nikula et al 2008). …”
Section: Moose Damage Was the Highest In Pine-dominated Mesic And Submentioning
confidence: 99%
See 2 more Smart Citations
“…Fertile habitats offer moose not only better quality and a larger quantity of food but also a variety of alternative food plants (Niemelä and Danell 1988;Heikkilä 1990;Heikkilä and Härkönen 1993;Månsson 2009;Nikula et al 2008). Pine stands mixed with deciduous seedlings seem to be attractive pastures for moose (Heikkilä 1990;Vehviläinen and Koricheva 2006), especially when birches are overtopping the pine seedlings (Nikula et al 2008). …”
Section: Moose Damage Was the Highest In Pine-dominated Mesic And Submentioning
confidence: 99%
“…food patch, may depend on both the availability of food within the patch and the spatial arrangement of food patches at broader spatial scales, such as an animal's home range. Earlier studies have indicated that resource selection by moose also occurs at several levels of hierarchy in the following order: a landscape (Nikula et al 2004), home range (Cassing et al 2006), food patch and food plant (Berqvist et al 2012;Nikula et al 2008), although it has been suggested that the food selection of moose mainly occurs at the food plant level (Danell et al 1991;Vehviläinen and Koricheva 2006;Berqvist et al 2012). From the point of view of moose damage risk, multi-scale resource selection suggests that underlying factors that affect browsing risk at the plantation or plant level may originate from larger scale processes or factors and should thus be taken into account in the moose damage risk assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their meta-analysis comparing insect herbivory in pure vs. mixed stands, Jactel and Brockerhoff (2007) found twenty-one studies where more palatable host trees were included in the mixture and these mixed stands were more damaged overall than pure stands. The presence of a preferred species (high quality food resource) in a mixed stand increased the level of damage on less preferred species (low-quality food) by mammalian herbivores such as vole and moose (Pusenius et al, 2003;Vehviläinen and Koricheva, 2006). The intensity of Armillaria damage increases with the number of susceptible conifer species in mixed plantations (Gerlach et al, 1997).…”
Section: Stand Compositionmentioning
confidence: 99%
“…However, not only specific preferences but also the surrounding landscape matrix will affect the probability of an individual seedling being browsed (Hornberg 2001;Edenius et al 2002;Bergman et al 2005). Browsing tends to be more intense in mixed species stands and, unsurprisingly, most severe in stands dominated by mixtures of attractive species (Vehviläinen and Koricheva 2006;Milligan and Koricheva 2013).…”
Section: Introductionmentioning
confidence: 99%